Analysis of The Influence of Liquidity on Investment on Investment: Comparison of Petrosea Data 2022-2023 - Salsabilah Al Fitri; Riska Nur Fauziyah; Alfi Manzilatur Rohmah; Muhammad Alkirom Wildan (Badan Penerbit STIEPARI Press, 2025)
This study aims to examine the influence of liquidity on investment at PT Petrosea Tbk during the period of 2022-2023. Liquidity is measured using the current ratio, quick ratio, and cash ratio, which reflects the company's ability to meet short-term obligations as well as support investment activities. The research data were obtained from the company's annual financial reports and relevant market information. A quantitative method was employed to analyze the relationship between liquidity and investment levels, while also considering other variables such as profitability and company size. The results indicate that liquidity has a positive and significant effect on investment. Improved liquidity encourages the growth of the company's investments, which ultimately contributes to business development. These findings highlight the importance of effective liquidity management as a strategic approach to supporting sustainable investment and provide recommendations for management in formulating optimal investment policies.